Insights on the role of cytokines in carious lesions - Goncalves, Lucelia Lemes; kim, Eui; Bortolatto, Janaina Freitas; Buzalaf, Marilia Rabello; Alreshaid, Lulwah; Prakki, Anuradha (Brazilian Dental Science, 2023)
Objectives: The dentin-pulp immune response to caries pathogenesis is still poorly understood due to the complexinterplay of the involving processes. The aim of this review was to explore the role of cytokines and its relevance inthe pathogenesis of dental caries. Results: Dental caries can result in a host inflammatory response in the dentalpulp, characterized by the accumulation of inflammatory cells leading to the release of inflammatory cytokinessuch as Interleukin-4 (IL-4), Interleukin (IL-6), Interleukin-8 (IL-8) and Tumor necrosis factor–a (TNF-a). IL-4seems to be correlated to the depth of carious lesions; IL-6 is strongly correlated to caries disease and is considereda potent biomarker; IL-8 can be a potent biomarker for both caries and other changes present in the pulp and,its release is correlated to TNF-a and IL-6; TNF-a plays an important role not only in caries progression, but alsoin other pathological processes. Conclusion: Specific mediators have a great potential to serve as biomarkersalluding to the presence and progress of caries disease, urging further investigations in the field.KEYWORDSBiomarkers; Cytokines; Dental caries; Dental pulp; Interleukins.